1999
DOI: 10.1212/wnl.53.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Deficient activation of the motor cortical network in patients with writer’s cramp

Abstract: Deficient activation of premotor cortex and decreased correlation between premotor cortical regions and putamen suggest a dysfunction of the premotor cortical network in patients with writer's cramp possibly arising in the basal ganglia. The dysfunction is compatible with a loss of inhibition during the generation of motor commands, which in turn could be responsible for the dystonic movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
127
3
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(143 citation statements)
references
References 42 publications
12
127
3
1
Order By: Relevance
“…13 Although BG activity during tapping (defined as percent-signal change from pre-tapping activity) was also greater in patients in this study, the sustained activity observed during rest can be more confidently attributed to dystonic pathophysiology, because secondary variables during movement itself (e.g., task difficulty, performance) may confound interpretation of patient/control differences. In addition, our finding may explain why previous imaging studies have not detected abnormal increases in BG activity during movement in FHD patients, 6,8,10 because standard "task versus rest" contrast analyses assume that the fMRI signal returns to pretask levels during posttask rest periods. This is the first demonstration of abnormally sustained BG activity after motor task performance in FHD patients.…”
Section: Fig 2 Hemodynamic Time Courses Illustrating That Rest Blockmentioning
confidence: 65%
See 1 more Smart Citation
“…13 Although BG activity during tapping (defined as percent-signal change from pre-tapping activity) was also greater in patients in this study, the sustained activity observed during rest can be more confidently attributed to dystonic pathophysiology, because secondary variables during movement itself (e.g., task difficulty, performance) may confound interpretation of patient/control differences. In addition, our finding may explain why previous imaging studies have not detected abnormal increases in BG activity during movement in FHD patients, 6,8,10 because standard "task versus rest" contrast analyses assume that the fMRI signal returns to pretask levels during posttask rest periods. This is the first demonstration of abnormally sustained BG activity after motor task performance in FHD patients.…”
Section: Fig 2 Hemodynamic Time Courses Illustrating That Rest Blockmentioning
confidence: 65%
“…8 In this study, we aimed to detect BG abnormalities in FHD patients by capitalizing on the spatiotemporal resolution of functional magnetic resonance imaging (fMRI). Specifically, we evaluated hemodynamic time courses in the BG and primary sensorimotor cortices at intervals before, during, and after FHD patients performed finger-tapping tasks.…”
Section: Ann Neurol 2004;55:744 -748mentioning
confidence: 99%
“…The exact pathophysiology of writer's cramp remains unknown. Structural changes in the sensorimotor cortex, basal ganglia and cerebellum (Garraux et al 2004;Egger et al 2007), abnormal activation in the basal ganglia-premotor cortex network during voluntary movements (Ibanez et al 1999), deficient inhibition at multiple levels of the motor system (Hallett 2006), impaired sensorimotor integration (Abbruzzese and Berardelli 2003), and excessive motor cortical plasticity (Quartarone et al 2006) have all been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced inhibition of motor cortex occurs with writer's cramp. 39,80 Consistent with these physiological studies, individuals with writer's cramp exhibit reduced GABA levels in cortex. 81 As with many forms of dystonia, increased excitability or reduced inhibition is present at spinal and brainstem levels with writer's cramp.…”
Section: Focal Hand Dystoniamentioning
confidence: 55%
“…Most imaging studies in both generalized and focal dystonias report that the same brain regions exhibit increased glucose uptake or blood flow. 23,80,85,89,[123][124][125]127,173,174 In virtually all cases of primary dystonia, there is dysfunction of the thalamus, frontal cortex, cerebellum, and basal ganglia, particularly the striatum. These altered activity patterns at least partially reflect a reduction in cortical inhibition.…”
Section: Implications Of Animal Models Of Focal Dystoniamentioning
confidence: 99%